2003
DOI: 10.1111/j.1440-1703.2003.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigment dynamics and autumn leaf senescence in a New England deciduous forest, eastern USA

Abstract: The leaves of woody plants at Harvard Forest in Central Massachusetts, USA, changed color during senescence; 70% (62/89) of the woody species examined anatomically contained anthocyanins during senescence. Anthocyanins were not present in summer green leaves, and appeared primarily in the vacuoles of palisade parenchyma cells. Yellow coloration was a result of the unmasking of xanthophyll pigments in senescing chloroplasts. In nine red-senescing species, anthocyanins were not detectable in mature leaves, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
180
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(202 citation statements)
references
References 61 publications
17
180
1
4
Order By: Relevance
“…The results indicated that both studied traits were significantly affected by the environment. This might be due to the environmental factors such as UV-A, UV-B, temperature, light intensity, nutrition and moisture regulated the synthesis of anthocyanin in leaves (LEE et al, 2003;SCHABERG et al, 2003;TOSSI et al, 2011;WANG et al, 2012). In addition, highly significant difference between generations on the traits were detected, especially between parental lines (Figure 1).…”
Section: Resultsmentioning
confidence: 83%
“…The results indicated that both studied traits were significantly affected by the environment. This might be due to the environmental factors such as UV-A, UV-B, temperature, light intensity, nutrition and moisture regulated the synthesis of anthocyanin in leaves (LEE et al, 2003;SCHABERG et al, 2003;TOSSI et al, 2011;WANG et al, 2012). In addition, highly significant difference between generations on the traits were detected, especially between parental lines (Figure 1).…”
Section: Resultsmentioning
confidence: 83%
“…4). This increase in redness may be due to the build-up of anthocyanin pigments that cause the red colouration of senescing leaves, also a distinct feature of deciduous forest canopies in autumn (Hoch et al, 2001;Lee et al, 2003;Gould, 2004). This species, W. laevis, may be found further north in semi-deciduous and deciduous vegetation communities that are connected floristically to the rainforests of the Daintree region.…”
Section: Tropical Rainforestmentioning
confidence: 99%
“…Carotenoids are not the only pigments responsible for autumn colors; anthocyanins often accumulate (Lee et al, 2003), giving rise to dark-reddish leaf colors, and have been proposed to function as light protectants during the nutrient recycling of senescing leaves (Feild et al, 2001;Hoch et al, 2003). Therefore, we quantified anthocyanin levels to see whether they changed during autumn senescence in aspen leaves.…”
Section: Dynamic Changes In Carotenoid and Anthocyanin Metabolismmentioning
confidence: 99%
“…Every autumn deciduous trees need to shed their leaves and prepare for the winter. Autumnal senescence is spectacular in many trees, when leaves change color from green to yellow and/or red (Lee et al, 2003). The different colors arise from the preferential degradation of chlorophylls over carotenoids and the synthesis of red-colored pigments like anthocyanins (Goodwin, 1958;Lichtenthaler, 1987).…”
mentioning
confidence: 99%